The Influence of Family and Pyramidal Ownership on Corporate Diversification in Chile - Espinosa-Mendez, C (Elsevier Inc., 2018)
In this paper we analyse the moderating effects of family nature and pyramidal ownership on the relationship between corporate diversification and performance in Chilean companies. Using a sample of 104 companies listed on the Santiago Stock Exchange between 2005 and 2016, we report a diversification discount. Second, we find that when firms are owned by a family, the relationship between performance and diversification is positive. However, when family ownership is pyramidal, the relationship between performance and diversification becomes negative. © 2017 Elsevier Inc.